Проблемы системного планирования подземного пространства мегаполисов - Панкратова, Н.Д.; Гайко, Г.И.; Кравец, В.Г.; Савченко, И.А. (Проблемы управления и информатики, 2016)
З системних позицій розглянуто сучасні тенденції розвитку підземного простору мегаполісів; виділено комплексну природно-технічну геосистему «геоурбаністика–геологічне середовище», що відкриває можливості для впровадження системної методології освоєння підземного простору, збільшення обсягів та оптимізації ризиків підземного будівництва. Для об'єктивного обгрунтування майбутнього розвитку підземних мегаполісів використовується метод морфологічного аналізу. With the system positions the modern trends of underground space development of megacities are considered. It is highlighted the complex natural and technical geosystem «geourbanistics–geological environment», which opens up opportunities for the introduction of a systematic methodology of underground space development, increasing the volume and risk optimization of underground construction. For an objective justification of the future development of underground megapolises the method of morphological analysis is involved.